Relative effects of plasma, fibrinogen concentrate, and factor XIII on ROTEM coagulation profiles in an in vitro model of massive transfusion in trauma. (18th August 2017) - Schmidt, David E.; Halmin, Märit; Wikman, Agneta; Östlund, Anders; Ågren, Anna
Abstract: Massive traumatic haemorrhage is aggravated through the development of trauma-induced coagulopathy, which is managed by plasma transfusion and/or fibrinogen concentrate administration. It is yet unclear whether these treatments are equally potent in ensuring adequate haemostasis, and whether additional factor XIII (FXIII) administration provides further benefits. In this study, we compared ROTEM whole blood coagulation profiles after experimental massive transfusion with different transfusion regimens in an in vitro model of dilution- and transfusion-related coagulopathy. Healthy donor blood was mixed 1 + 1 with six different transfusion regimens. Each regimen contained RBC, platelet concentrate, and either fresh frozen plasma (FFP) or Ringer's acetate (RA). The regimens were further augmented through addition of a low- or medium-dose fibrinogen concentrate and FXIII. Transfusion with FFP alone was insufficient to maintain tissue-factor activated clot strength, coincidental with a deficiency in fibrin-based clot strength. Fibrinogen concentrate conserved, but did not improve coagulation kinetics and overall clot strength. Only combination therapy with FFP and low-dose fibrinogen concentrate improved both coagulation kinetics and fibrin-based clot strength. Administration of FXIII did not result in an improvement of clot strength. In conclusion, combination therapy with both FFP and low-dose fibrinogen concentrate improved clotting time and produced firm clots, representing a possible preferred first-line regimen to manage trauma-induced coagulopathy when RBC and platelets are also transfused. Further research is required to identify optimal first-line transfusion fluids for massive traumatic haemorrhage.